Breton's Nadja: A Spiritual Ethnography - Louis Tremaine (Studies in 20th & 21st Century Literature, 1976)
A comparison of Breton's Nadja (1928, revised 1962) with Carlos Castaneda's recent ethnographic studies provides numerous insights into the structure of Breton's work. The narrative technique of Nadja combines documentary and literary modes, reflecting the double focus of the narrator's personal quest for self-knowledge and quasi-scientific quest for knowledge of external surrealistic phenomena. Nadja offers Breton a personal relationship capable of integrating, through an essentially cultural process, the subjective and objective levels of his investigation, but his fear of madness causes him to reject this personal involvement. He thereby rejects the only source of the integrative understanding he seeks, turning instead to the "convulsive beauty" of an irresolvable double focus on self and other.
Keywords: Brenton; Carlos Castaneda; Nadja; narrative technique; ethnographic studies; ethnological expedition; external surrealistic phenomena